2014
DOI: 10.1002/chem.201402394
|View full text |Cite
|
Sign up to set email alerts
|

1,4‐Addition of TMSCCl3 to Nitroalkenes: Efficient Reaction Conditions and Mechanistic Understanding

Abstract: Improved synthetic conditions allow preparation of TMSCCl3 in good yield (70 %) and excellent purity. Compounds of the type NBu4X [X=Ph3SiF2 (TBAT), F (tetrabutylammonium fluoride, TBAF), OAc, Cl and Br] act as catalytic promoters for 1,4-additions to a range of cyclic and acyclic nitroalkenes, in THF at 0–25 °C, typically in moderate to excellent yields (37–95 %). TBAT is the most effective promoter and bromide the least effective. Multinuclear NMR studies (1H, 19F, 13C and 29Si) under anaerobic conditions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…% tetramethylpiperidinyloxide (TEMPO) to provide acceptable yields. This behaviour is attributed to aerobic triggered competing radical reactions, which we have noted before . Control reactions (absence of anionic promotors and use of other radical traps) indicated that the TEMPO does act as an inhibitor in this case…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…% tetramethylpiperidinyloxide (TEMPO) to provide acceptable yields. This behaviour is attributed to aerobic triggered competing radical reactions, which we have noted before . Control reactions (absence of anionic promotors and use of other radical traps) indicated that the TEMPO does act as an inhibitor in this case…”
Section: Resultssupporting
confidence: 67%
“…With 1 now accessible cleanly and in large quantities, its reactivity and potential as a cyclopropanation reagent was explored. Cyclic nitroolefin ( 2 a ) was picked as the model alkene for the reaction, as nitroolefins have been reported as potent Michael acceptors for TMSCCl 3 ,. Table outlines the effects of different promotors on its cyclopropanation reaction with 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trichloro(trimethylsilyl)methane2 is an attractive heat‐ and air‐stable reagent that provides a milder equivalent of the [CCl 3 ] – carbanion for use in 1,2‐ and 1,4‐additions to π‐systems such as aldehydes and ketones,3 imines4 acrylates5 and nitroalkenes 6. In 2014 we were able to contribute an improved synthesis of TMSCCl 3 that enabled us to expand the scope of 1,4‐additions to nitro olefins,7 yet the use of other Michael acceptors with this reagent remains rather underexplored. While additions of trichloromethyl radicals to electron‐rich alkenes have been known since the pioneering work of Kharasch in the late 1940s,8 additions of “ · CCl 3 ” units to electron‐deficient alkenes appear limited to acrylonitrile and methyl acrylate.…”
Section: Introductionmentioning
confidence: 99%